ANALISIS PENDAFTARAN MEREK DAGANG TERHADAP KELAS BARANG BAGI PELAKU USAHA KECIL - Ratu Ratna Karompot (Maleo Law Journal, 2018)
Brand registration to small business actors is very important to get protection and protection from the flood and the flood of famous products, which became the masal ah is when it has been registered to have the same class of goods with the famous brand class or that has been preceded to register the brand either the equation in essence or equality on the whole, this is what must be understood from the class of goods to the brand goods. Because generally small business actors when finding the problem do not want to be bothered and still do not want to change the trademark on the grounds because the brand of goods have many who know, and do not understand the flow of registration, because although not yet registered subject to class goods. And also the lack of understanding about the brand itself. This article examines whether the Law no. 15 of 2001 after being substituted into Law No. 20 of 2016 on Trademarks and Geographical Indications has provided protection to small business actors, especially in the Brand class. It is important to examine to provide justice and protection to both the owners of famous brands, as well as the brand new owners. Keyword : Class Goods, Brand Goods.